VARIABILITAS MUSIMAN SUHU PERMUKAAN LAUT DAN ANGIN DI LAUT ARAFURA - RIUPASSA, YOPI; WATTIMURY, JUSUPH J (Prodi Ilmu Kelautan Fakultas Perikanan dan Ilmu Kelautan Universitas Pattimura, 2022)
Research on sea surface temperature (SST) and wind in the Arafura Sea is very important to answer various processes and phenomena that occur in the water column, for example upwelling and downwelling phenomena, the influence of monsoon winds, ENSO and LaNina phenomena, mixing of water masses, forecasting fishing areas, determination of marine cultivation areas, and so on. This study aims to examine the spatial distribution and variability of sea surface temperature (SST) and wind and to examine the correlation of SST with wind speed and direction in the Arafura Sea. SST data is obtained from the AQUA MODIS satellite which is downloaded on the website http://oceancolor.gsfc.nasa.gov. Wind data obtained from the site: ftp://ftp.ifremer.fr/ifremer/cersat. The results of the analysis show that the SST in the Arafura Sea varies seasonally with a range of 23–34oC and a variation of 3.01-4.60%. The wind speed ranges from 0.02-10 m/s with a variation of 40.07-47.76%. There is a strong correlation between SST and wind speed and direction based on latitude and longitude. The correlation between wind speed and SST ranges from -0.01 to -0.87, while the correlation between wind direction and SST ranges from 0.52 and -0.71. In certain waters there is a positive linear correlation of SST with wind direction of 0.18-0.78